2018
DOI: 10.1111/bju.14569
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐term safety and efficacy of the ALTIS® single‐incision sling for female stress urinary incontinence: less mesh, same results

Abstract: Objective To analyse the mid‐term safety and efficacy of the ALTIS® single‐incision sling (Coloplast Corp., Minneapolis, MN, USA) for female stress urinary incontinence (SUI). Patients and Methods We conducted a prospective, single‐arm, unsponsored, observational single‐centre trial in a cohort of patients undergoing SUI surgery with the ALTIS procedure. All patients were diagnosed according to clinical reports, physical exploration and urodynamics. Body mass index (BMI) was categorised according to World Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 28 publications
4
17
1
Order By: Relevance
“…Most of the scientific publications are retrospective observational studies, 13,15 and prospective single-center 16,17 or multicenter. 18 Our work is a prospective observational single-center study with a 6-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the scientific publications are retrospective observational studies, 13,15 and prospective single-center 16,17 or multicenter. 18 Our work is a prospective observational single-center study with a 6-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…18 Our work is a prospective observational single-center study with a 6-year follow-up. The literature reviewed reports follow-ups at 1year, 13,16,19,20 2years 17,18 and 3years. 15 Our work includes women with a history of pure SUI and MUI with a predominance of stress incontinence, a positive cough test in consultation with urethral hypermobility, and failed or unwanted previous conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The objective and subjective cure rates were promising in both the obese and non-obese groups without significant differences. Morán et al conducted a prospective, single-arm study with a mean follow-up period of 22.3 months and reported objective and subjective cures of 83% and 88% irrespective of the BMI [7]. Oliveira et al conducted a prospective, single-arm study with a mean follow-up period of 12 months and reported postoperative improvement rates in of 94% and 90% in women with and without obesity, respectively [15].…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between obesity and SUI has been well documented, relatively few studies have investigated the safety and efficacy of surgical treatments among overweight and obese women. A mid-urethral sling is currently the most effective treatment for incontinence [7]. The first mid-urethral sling, tension-free vaginal tape, was developed by Ulmsten in 1996 with promising long-term results [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation